Suriname and the CARICOM : the bumpy road to integration - Donner, Walther (Laetitia Books RotterdamNL, 2010)
States that after 15 years, Suriname is yet to see tangible benefits from its membership of the Caribbean Community. Explores the hurdles Suriname has to overcome to play a more sensible role in the Community. Concludes that its mindset stands in the way of a better performance.